THE IMPLEMENTATION AND THE STUDENT'S RESPONSES OF GUIDED QUESTION TECHNIQUE IN TEACHING WRITING RECOUNT TEXT - Sinta Pertiwi; Evie Kareviati (PROJECT (Professional Journal of English Education), 2021)
The research is aimed to investigate the implementation and to find out student’s responses to the guided questions technique in teaching writing recount text. The research used descriptive qualitative method. The data was obtained from observation and questionnaire. The research was conducted at SMPN 5 Cimahi which the participant was the 35 students of VIII – G. The result of the research showed that the guided question technique was implemented under the theory. It can be seen from the use of basic questions to gathering the ideas and the steps of implementing the guided question technique were done while the teaching-learning process. Guided questions technique also helps students in understanding the material. Meanwhile, the students gave a positive response toward the guided questions technique's implementation with 76.3% of students agree that the guided question technique is interesting and easy to use. Moreover, with the average 97%, attention aspect being the highest average indicator which can be illustrated that the guided questions technique was interesting and enjoyable. Keywords: Writing, Recount text, Guided question, Student's response